Digitalization and Tax-Motivated Income Shifting - Fau, Devenni Putri; Kurniawati, Lestari (UI Scholars Hub, 2022)
Numerous studies show that the tax rate difference between parent and subsidiaries as well as among subsidiaries acts as the incentive for income shifting between multinational corporations (MNCs). Digital business models that emerged as an impact of digital transformation may exacerbate income shifting by MNCs. However, empirical studies to support the relation between digital business models and income shifting is still scarce. Thus, this study examined whether Indonesia’s foreign-owned manufacturing companies shift income in respect to its foreign-parent tax rate and if the level of digitalization exacerbates the practice. This study used the income-shifting approach by Hines and Rice (1994) modified by Purba (2018) extended with the level of digitalization which is intangible asset intensity. Using a panel data regression model of public-listed manufacturing companies from 2011 to 2019, this study found no evidence of income shifting between foreign-owned Indonesian companies with its parent overseas. Moreover, using moderated regression analysis, this research found that the level of digitalization did not strengthen the influence of tax rate to income shifting. Thus, it concluded that digitalization did not influence income shifting practice. While the results were inconsistent, it did not rule out the possibility of income shifting between affiliates in a group and/or the utilization of other channels of income shifting such as debt and transfer pricing. Furthermore, this study may initiate future studies in the relationship between income shifting and digitalization by employing different measurement or expanding the research’s samples.